Does using a laser improve outcomes of conventional circumcision in adult and children populations? Results from a systematic review and meta‐analysis. (2nd November 2022) - Scarcella, Simone; Law, Yu Xi Terence; Bravi, Carlo Andrea; Piazza, Pietro; Heldwein, Flavio L.; Ronchi, Piero; Lacetera, Vito; Beatrici, Valerio; Gauhar, Vineet; Castellani, Daniele
Abstract: Background: Male circumcision is a well‐known old surgery, and several recently developed techniques have been scaled up, including the introduction of laser technology, as alternative approaches to overcome morbidity of conventional surgery scalpel/suture method Objectives: We aimed to perform a systematic review and meta‐analysis of studies comparing laser circumcision versus conventional circumcision technique in terms of perioperative outcomes and efficacy (complications, unacceptable appearance, reoperation rate) both in children and adults. Materials and methods: This review was performed following the 2020 Preferred Reporting Items for Systematic Reviews and Meta‐Analyses framework. Continuous variables were analyzed using the inverse variance of the mean difference with a random effect, 95% confidence interval (CI), and p ‐value. The incidence of complications, unacceptable appearance, and reoperation rate were pooled using the Cochran‐Mantel‐Haenszel Method with the random effect model and reported as odds ratio (OR), 95% CI, and p ‐value. Significance was set at p ‐value ≤0.05 and 95%CI. Results: Seven studies were included. In comparison to the conventional circumcision, laser circumcision shoved lower visual analogue score at 24‐h, and 7 days after surgery, a lower rate of overall complication rate (OR 0.33, 95% CI 0.24–0.47, p  < 0.001), scarring (OR 0.09, 95% CI 0.02, 0.41, p  = 0.002), and unacceptable appearance (OR 0.09, 95% CI 0.05, 0.15, p  < 0.001). We found no statistically significant difference in surgical time, and incidence of bleeding, infection, wound dehiscence, and reoperation rate. Discussion and conclusion: Our review infers that laser‐assisted circumcision is certainly a safe and strong contender as the procedure of choice in both children and adult populations.